Evaluasi Kinerja Instalasi Pengolahan Air Limbah Rumah Sakit X di Jakarta Pusat - Rizky Fathan Witjaksono; Mohammad Rangga Sururi (Jurnal Serambi Engineering, 2023)
Hospital X has an WWTP which since its inception until now has never been evaluated and there is a recycling tub that cannot function normally and there is a calculation error in the water mass balance to minimize the impact of wastewater on environmental pollution, so an evaluation of the WWTP unit is carried out. The purpose of this study is to evaluate WWTP and provide suggestions related to optimizing wastewater treatment at X Hospital to improve wastewater removal performance. This study refers to design criteria and quality standards based on literature and evaluation of existing conditions using secondary data and primary data. Based on the evaluation results of the WWTP, it was found that the wastewater discharge was 166.3 m3/day, has an efficiency that is included in the category of very efficient and efficient in processing wastewater pollutant parameters so that the wastewater treatment process runs well, and there is equalization, the first and second settling tanks, activated sludge, trickling filter, filtration, disinfection and recycling did not meet the design criteria so a recalculation was carried out. The solution provided is to tighten monitoring and testing of the condition of the quality of wastewater coming out of the WWTP unit by changing the sampling test method, re-measuring the quality of influent wastewater, improving the workings of the IPAL unit according to the applicable Standart Operation Procedure (SOPs).